Petrological Studies of Yamato-74 Meteorites (2) - Kimura, Makoto; Yagi, Kenzo; Oba, Yoshio (1978)
P(論文) Six Yamato meteorites collected in 1974 in Antarctica are petrographically investigated. All of them are ordinary chondrites, recrystallized and shocked to various extent. From the texture and the chemical composition of olivine and orthopyroxene, Yamato-74079,-74155,-74190,-74371,-74418 and -74647 meteorites are classified respectively as H5,H4,L6,H5,H6 and H5 of VAN SCHUMUS and WOOD (1967). Difference in recrystallization of the matrices and the mineralogy is noticed between meteorites belonging to different petrologic types. departmental bulletin paper